Heterocyclic chemistry at a glance - Joule, John. A. (John Arthur); Mills, K. (Keith) (Chichester, West Sussex ; Hoboken : Wiley, 2012)
This expanded second edition provides a concise overview of the main principles and reactions of heterocyclic chemistry for undergraduate students studying chemistry and related courses. Using a successful and student-friendly "at a glance" approach, this book helps the student grasp the essence of heterocyclic chemistry, ensuring that they can confidently use that knowledge when required. The chapters are thoroughly revised and updated with references to books and reviews; extra examples and student exercises with answers online; and color diagrams that emphasize exactly what is happening in.
Heterocyclic Nomenclature -- Structures of Heteroaromatic Compounds -- Common Reaction Types in Heterocyclic Chemistry -- Palladium in Heterocyclic Chemistry -- Pyridines -- Diazines -- Quinolines and Isoquinolines -- Pyryliums, Benzopyryliums, Pyrones and Benzopyrones -- Pyrroles -- Indoles -- Furans and Thiophenes -- 1,2-Azoles and 1,3-Azoles -- Purines -- Heterocycles with More than Two Heteroatoms: Higher Azoles (5-Membered) and Higher Azines (6-Membered) -- Heterocycles with Ring-Junction Nitrogen (Bridgehead Nitrogen) -- Non-Aromatic Heterocycles -- Heterocycles in Nature -- Heterocycles in Medicine -- Applications and Occurrences of Heterocycles in Everyday Life.
Includes index.
Print version record and CIP data provided by publisher.
Keywords: Heterocyclic chemistry -- Textbooks; Chemistry -- Textbooks; SCIENCE -- Chemistry -- Organic; Chemistry; Heterocyclic chemistry; Electronic books; Textbooks